Heterogeneous Puumala orthohantavirus situation in endemic regions in Germany in summer 2019. Issue 2 (29th November 2019) - Binder, Florian; Drewes, Stephan; Imholt, Christian; Saathoff, Marion; Below, Diana Alexandra; Bendl, Elias; Conraths, Franz J.; Tenhaken, Peter; Mylius, Maren; Brockmann, Stefan; Oehme, Rainer; Freise, Jona; et al.
Abstract: Puumala orthohantavirus (PUUV) causes most human hantavirus disease cases in Europe. PUUV disease outbreaks are usually synchronized Germany‐wide driven by beech mast‐induced irruptions of its host (bank vole, Myodes glareolus ). Recent data indicate high vole abundance, high PUUV prevalence and high human incidence in summer 2019 for some regions, but elsewhere values were low to moderate. This significant lack of synchrony among regions in Germany is in contrast to previous studies. Health institutions need to be informed about the heterogeneous distribution of human PUUV infection risk to initiate appropriate actions.